DAMPAK FASILITAS PENUNJANG USAHATANI TERHADAP MOTIVASI PETERNAK PLASMA AYAM BURAS DI KABUPATEN BANTUL IMPACT OF SUPPORTING FACILITY ON MOTIVATION OF PLASMA NATIVE CHICKEN FARMERS AT BANTUL REGENCY - Setiana, Lucie (Pembangunan Pedesaan, 2005)
Aims of this research were to know: 1) impact of supporting facility on motivation of plasma native chicken farmers and 2) correlation between motivation of the farmers and their facility, expectancy, and objectives. To determine the motivation rate before and after receiving facility, ujit motivation index was used including responsibilities, activities, creativity and group cooperation factors, and then continued with sign ujit. Correlation coefficient kisaran Spearmanâs analysis was used to know correlation between inter-variables and motivation. Result of the research showed that there was significant (p